Inhibitors of Fibrinolysis in Amniotic Fluid - Walker, J E; Campbell, D M; Ogston, D (Thrombosis and Haemostasis, 1980)
Amniotic fluid inhibited the fibrinolytic, amidolytic and esterolytic activity of urokinase. Kinetic studies with AGLMe demonstrated non-competitive inhibition. A major part of the inhibitory activity could be separated from α1-antitrypsin by ion-exchange chromatography on DEAE-Sephadex A-50. Plasminogen activator prepared from porcine heart was not inhibited by amniotic fluid. Amniotic fluid also inhibited the caseinolytic and amidolytic activities of plasmin.
Keywords: Amniotic fluid; Inhibitors of urokinase; Inhibition of fibrinolysis